Gender Prescribed Occupations and the Wage Gap - Matteo Broso; Andrea Gallice; Caterina Muratori (Global Labor Organization (GLO), 2024)
Men and women often sort into different jobs, and male-dominated jobs typically pay more than female-dominated ones. Why is that the case? We propose a model where workers have heterogeneous attitudes with respect to the social norms that define gender prescribed occupations and face endogenous social costs when entering jobs deemed "appropriate" for the other gender. We show that: (i) workers trade off identity and wage considerations in deciding where to work; (ii) asymmetric social norms contribute to the gender pay gap by deterring women from entering higher-paying male-dominated sectors; (iii) breaking social norms generates positive externalities, reducing social stigma for everyone. Therefore, in equilibrium, there are too few social norm breakers.
Keywords: J24; J31; 330; Occupational Segregation; Wage Gap; Social Norms